Teaching to learning styles - Robbins, John; Wurzburg, Gerry (Virginia : Association for Supervision and Curriculum Development, 1992)
This program is based on several assumptions about learning and teaching style
Executive producer, Marcia D'Arcangelo ; editor, Judy White ; writer, John Robbins
Keywords: Study skills; Learning; Teaching